PEMANFAATAN KOMPOS UNTUK MENINGKATKAN HASIL STROBERI ORGANIK DI KOTA TOMOHON - Supit, J. M.J.; Kamagi, Y. E.B.; Kumolontang, W. (EUGENIA, 2016)
ABSTRACT  Study on compost utilization to support organic strawberry production in Tomohon has been performed to promote the use of compost (mixture of chicken manure and rice husk) in organic strawberry and to determine the compost dosage producing highest strawberry yield. Completely randomized design (CRD) with 4 (four) replicates  has been performed to apply various compost levels, namely 60 t/ha (SPo), 60 t/ha (SP1), 120 t/ha (SP2), 180 t/ha (SP3), and 240 t/ha (SP4). Data analysis has been conducted by means of analysis of variance (ANOVA) followed by the Least Significant Difference Test.  The results revealed the significant yield differences among treatments.  The highest result (28 fruits/ pot having 174.64 gram weight) was found in SP3 compost level (180 t/ha).Key words: compost, agricultural land Rurukan Tomohon, strawberries